PREDIKSI CURAH HUJAN DENGAN METODE KALMAN FILTER (Studi Kasus di Kota Semarang Tahun 2012) - Tika Dhiyani Mirawati; Hasbi Yasin; Agus Rusgiyono (Jurnal Gaussian, 2013)
The rainfall data is very interesting to be studied because it is constitutes one of the biggest factor that influence the climate on a region and human life sector. In this studies, the rainfall prediction is utilized by Kalman Filter method. The implementation of Kalman Filter analysis in this research is used for modelling and forecasting rainfall in Semarang city. This method provide a recursive solution to minimize error. Kalman Filter consists of state equation and observation equation. The forecasting result in 2012 showed that the prediction is close to the current data whereas in 2013 it increase which the maximum rainfall is 406 mm happening in February and the minimum rainfall is 35 mm happening in July. Overall, the average rainfall in 2013 at Semarang city is 196,25 mm